Forecasting The Modernisation Of Indonesia’s Defence Equipment Under The Shadow Of Aukus: A Monte Carlo Simulation Of Defence Budget Scenarios - Pardamean Lasniroha Siahaan, Martua; Murniasari, Mira; Ayu Permatasari, Diah (Jurnal Syntax Fusion, 2025)
This study examines Indonesia's defense equipment modernization in the evolving Indo-Pacific security environment shaped by the establishment of AUKUS (Australia–United Kingdom–United States security pact). Using Monte Carlo Simulation (MCS), the research estimates the impact of different defense budget allocation scenarios on Indonesia's capability development, focusing on air, naval, and cyber defense. The model incorporates uncertainties such as GDP growth, inflation, exchange rates, procurement costs, technological advancements, and regional security dynamics from 2025 to 2045. Three scenarios are analysed: (1) Conservative, with defense spending limited to 2–3% of GDP; (2) Moderate, with gradual increases to 3–3.5% of GDP; and (3) Ambitious, maintaining 4% of GDP. Findings indicate that under the Conservative Scenario, Indonesia faces a 65% probability of failing to meet Minimum Essential Force (MEF) targets by 2035, particularly in naval and air power. The Moderate Scenario shows a 55% probability of meeting MEF by 2035, although cyber defense remains underfunded. In contrast, the Ambitious Scenario provides a 70% probability of Indonesia surpassing MEF targets and achieving advanced deterrence capabilities by 2045. The results demonstrate that fiscal commitment is the most decisive factor in shaping modernization outcomes, although efficiency in procurement, domestic defense industry growth, and regional partnerships can significantly influence success. While AUKUS heightens arms competition, it also presents opportunities for Indonesia to pursue strategic cooperation and technology access. Overall, MCS offers a probabilistic framework that underscores the importance of sustained budgetary support, adaptive strategies, and domestic industrial development in advancing Indonesia's long-term defense modernisation.